La biodiversité dans l’aménagement du territoire en Guyane française - Marc Galochet; Valérie Morel (VertigO, 2015)
The aim of this paper is to understand the place of the biodiversity in the territorial policies in French Guiana. This amazonian ultramarine french department, presented as one of the five wild zones of high biodiversity at world level, constitutes a laboratory of mobilization of biodiversity in the territory management. If during these last two decades, the biodiversity especially remained a scientific concept, today it transposes into territory projects to the point to see appearing many documents of planning and statutory and contractual plans integrating the biodiversity. However, is the French Guiana ready to overtake the conservative biodiversity so that the biodiversity becomes a tool of territorial development ?